Protein Supplementation Throughout 10 Weeks of Progressive Run Training Is Not Beneficial for Time Trial Improvement - Roberson, Paul A.; Romero, Matthew A.; Mumford, Petey W.; Osburn, Shelby C.; Haun, Cody T.; Vann, Christopher G.; Kluess, Heidi A.; Roberts, Michael D. (Frontiers in Nutrition, 2018)
INTRODUCTION: Protein supplementation is proposed to promote recovery and adaptation following endurance exercise. While prior literature demonstrates improved performance when supplementing protein during or following endurance exercise, chronic supplementation research is limited. METHODS: Runners (VO2peak=53.6±8.9 ml/kg/min) were counter-balanced into a placebo group (PLA; n=8) or protein group (PRO; n=9) based on sex and VO2peak, and underwent 10 weeks of progressive endurance training. Prior to training, body composition, blood cell differentials, non-invasive mitochondrial capacity using near-infrared spectroscopy, and a 5 km treadmill time trial (TT) were evaluated. Progressive training then commenced (5-10% increase in weekly volume with a recovery week following 3 weeks of training) whereby PRO supplemented with 25 g of whey protein following workouts and prior to sleep (additional 50 g daily). PLA supplemented similarly with a <1 g sugar pill. Following training, participants were reanalyzed for the aforementioned tests. RESULTS: VO2peak and initial 5 km TT were not significantly different between groups. PRO consumed significantly more dietary protein throughout the training period (PRO=132 g/d or 2.1 g/kg/day; PLA=84 g/d or 1.2 g/kg/day). Running volume increased significantly over time, but was not significantly different between groups throughout training. Blood measures were unaltered with training or supplementation. Mitochondrial capacity trended towards improving over time (time p=0.063) with no difference between groups. PLA increased lean mass 0.7 kg (p<0.05) while PRO experienced infinitesimal change (-0.1 kg, interaction p=0.049). PLA improved 5 km TT performance 6.4% (1 min 31 s), while PRO improved only 2.7% (40 s) (interaction p=0.080). CONCLUSION: This is the first evidence to suggest long-term protein supplementation during progressive run training is not beneficial for runners.